CR(VI) ION ADSORPTION USING ?-CARRAGEENAN BEADS ADSORBENT MODIFIED BY POLYETHYLENIMINE (PEI) AND GLUTARALDEHYDE (GA) - Rhea Amalia, Khalisha
Heavy metal pollution in the aquatic environment is a problem of global concern. Cr(VI) ions are classified as a group 1 carcinogen by the World Health Organization (WHO). Long-term exposure to Cr(VI) levels of more than 0.1 ppm can cause respiratory problems, liver, kidney, and cancer damage. Adsorption has been considered as a promising technology for removing toxic metals from industrial effluents and natural waters. Carrageenan is an anionic biopolymer which has an ester sulfate group on one of its carbon atoms. ?-carrageenan is one of the main groups of carrageenan which has a strong gel-forming character. In this research, the adsorbent of ?-carrageenan beads was modified with polyethyleneimine (PEI). PEI is a polymer containing primary, secondary, and tertiary amino groups. PEI is a water soluble, positively charged aliphatic polymer available in linier and branched forms. Due to its positive charge, PEI can coat the surface of the negatively charged ?-carrageenan beads and interact with Cr(VI) ions through electrostatic interactions. To increase the stability of the adsorbent, PEI is crosslinked with gluteraldehyde (GA). The beads have been successfully characterized using FTIR spectroscopy and SEM-EDS. Based on the results, the optimum adsorption conditions were obtained at pH 3, a contact time of 240 minutes, and the adsorbent dose of 2 g L–1. The adsorption of Cr(VI) ions following a pseudo second order adsorption kinetics model with an R2 value of 0.9982 with a rate constant of 9.94 × 10-4 mg L?1 min?1. The adsorption process followed the Langmuir adsorption isotherm model with an R2 value of 0.9955 and a maximum adsorption capacity of 180.38 mg g–1 at 323 K. The results of thermodynamic studies show that the adsorption process is exothermic and occurs spontaneously. The desorption studies of Cr(VI) ion using HNO3 0.1 M showed the reusability of the adsorbent.